High-performance ceramics. X : the 10th China International Conference on High-Performance Ceramics (CICC-10) : selected, peer reviewed papers from the 10th China International Conference on High-Performance Ceramics (CICC-10), November 4-7, 2017, Chang, China - Pan, Wei (Professor); Gong, Jianghong (Trans Tech Publications, 2018)
This book contains the papers presented at the Tenth International Conference on High-Performance Ceramics (CICC-10), which was held from November 4 to 7, 2017, in Nanchang, China. The Collection covers most aspects in the field of high-performance ceramics (advanced ceramics), including processing, microstructures, and properties of structural and functional ceramics. Especially, the papers gave an overview of the most recent development in high-performance ceramics in China.
Keywords: Ceramics -- Congresses.; elektronické knihy; electronic books